Business Intelligence, technology anxiety and Strategic Learning as Drivers of Strategic Decision-Making: The Mediating Role of Decision-Making Agility - Ahmed Sameer. N. Al-Thabit; Murtadha Abdul Ghafoor Nsaif; Anmar Shihab Ahmed (Decision Making: Applications in Management and Engineering, 2025)
This study examines the relationships between business intelligence (BI), strategic learning (SL), technology anxiety (TA), decision-making agility (DMA), and strategic decision-making (DM) in the Iraq’s IT sector. A quantitative research design has been considered and employed, and survey data were collected from 224 top officials from the targeted sector. The analysis was conducted using Smart PLS 4.0 to test both direct and mediating effects. However, the study also focuses on testing the measurement model before applying the structural equation modelling technique. The results show that DMA has a positive impact on strategic DM, and BI significantly enhances DMA but not DM on direct grounds. Moreover, it is observed that strategic learning tends to exert a positive influence on both DMA and DM, while TA shows no significant effect on the given constructs. Mediation analysis also additionally claiming that DMA plays a significant mediating role between SL and DM, and between BI and DM, respectively. These findings highlight the importance and organizational need of agility as a key mechanism through which learning and intelligence improve strategic decision-making in technology-driven organizations specifically in the Iraq region and in generally for the other regional economies. Besides, the limitations and future directions are also discussed.